P77 The Short Physical Performance Battery is Associated with Peripheral Muscle Dysfunction and Physical Activity in COPD. (19th November 2012) - Patel, MS; Mohan, D; Kon, SS; Canavan, JL; Polkey, MI
Abstract : Introduction and Objectives: Quadriceps muscle dysfunction and physical activity independently predict patient related outcomes including mortality in COPD. However, direct measurements in clinical practise are limited by time constraints, expertise and expense. The Short Physical Performance Battery (SPPB) is a simple objective tool scored out of 12, that evaluates lower extremity function by composite assessment of standing balance, habitual gait speed and timed sit-to-stand. Whilst the SPPB is predictive of adverse outcomes including nursing home admission and mortality in general populations, limited data are available in COPD; the relationship between the SPPB and exercise performance, peripheral muscle strength, muscle bulk and physical activity is of particular interest. We hypothesised that SPPB performance would relate to functional exercise performance, quadriceps strength, quadriceps bulk and physical activity. Methods: SPPB data was collected in 109 stable COPD patients (64M:45F). Other measurements included spirometry, body mass index (BMI), fat free mass (FFM) by bioelectrical impedance, six-minute walk test distance (6MWT), quadriceps muscle strength by volitional (QMVC) and non-volitional techniques (TwQ) and cross-sectional area of the rectus femoris by ultrasound (RFCSA). Physical activity level (PAL) was determined by the Sensewear armband worn over a 7 day period. Results: There was no relationship between SPPB performance and FEV1% predicted or BMI. Whilst SPPB performance correlated weakly with age (r=–0.21, p=0.03) and FFMI (r=0.21, p=0.03) a stronger relationship was seen with PAL (r=0.48, p<0.0001), 6MWT (r=0.64, p<0.0001), RFCSA (r=0.45, p<0.0001), QMVC/BMI (r=0.41, p<0.0001) and TwQ (r=0.44, p=0.004). Stratifying according to SPPB identified those with reduced quadriceps bulk (see figure 1 ), QMVC/BMI and physical activity. Conclusions: In COPD, SPPB performance is not related to lung function impairment. It detects those who are less active and those with reduced peripheral muscle strength and bulk. The SPPB may be a useful tool in predicting COPD patients at greater risk of future adverse events and those suitable for intervention.